Digitalization of Payments in Urban Society Indonesia - Nyimas Dewi Murnila Saputri; Fida Muthia; Melisa Ariani Putri (Universitas Muhammadiyah Yogyakarta, 2025)
This research investigates the influence of users' perceptions of usefulness and ease of use on their intention to adopt digital payment methods, with attitude serving as an intervening factor. By employing the Technology Acceptance Model (TAM), this study delivers meaningful input for technology developers and decision-makers to understand the key elements affecting users’ acceptance of digital payment platforms. Primary data for this study were obtained from a questionnaire of 200 urban communities in Indonesia that use digital payments in transactions using non-probability sampling techniques. This study used the SEM-PLS method using SmartPLS 3. The findings indicated that Perceived Usefulness (X1) does not exert a significant influence on Attitude (Y). However, Perceived Usefulness (X1) is known to be able to influence Behavior Intention (Z) directly. Attitude (Y) significantly affects Behavior Intention (Z). Perceived Ease of Use (X2) significantly influences Attitude (Y). Still, it cannot directly influence Behavior Intention (Z), which means that digital payments must be easy to use to shape supportive attitudes toward digital payments and increase intention to use. While enhancing perceived usefulness can directly increase users’ intention to adopt these technologies, improving ease of use is essential for fostering positive attitudes, which in turn shape behavioral intentions.